2011
DOI: 10.1016/j.imlet.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Sjögren's syndrome with Id3 conditional knockout mice

Abstract: The Id3 gene has been shown to play important roles in the development and function of broad tissue types including B and T cells. Id3 deficient mice develop autoimmune disease similar to human Sjögren's syndrome. Both B and T lymphocytes have been implicated to contribute to the disease phenotype in this disease model. In order to gain a better understanding of individual cell types in this disease model, we generated an Id3 conditional allele. An LckCre transgene was used to induce Id3 deletion in developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…Previous publications have confirmed that T cells play a critical role in disease initiation in Id3 −/− mice[7, 8], so we tested two key disease parameters in 12–24 week old Id3 −/− mice that lack αβ T cells, namely, lymphocytic infiltration and saliva production. Histological analysis of salivary gland tissues revealed that Id3 −/− mice lacking αβ T cells fail to develop the hallmark lymphocytic infiltration found in Id3 −/− mice (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications have confirmed that T cells play a critical role in disease initiation in Id3 −/− mice[7, 8], so we tested two key disease parameters in 12–24 week old Id3 −/− mice that lack αβ T cells, namely, lymphocytic infiltration and saliva production. Histological analysis of salivary gland tissues revealed that Id3 −/− mice lacking αβ T cells fail to develop the hallmark lymphocytic infiltration found in Id3 −/− mice (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Altered glandular homeostasis has been reported in Id3 −/− mice prior to the presence of lymphocytic infiltration, suggesting that additional factors likely contribute to the early exocrinopathy observed in this SS mouse model[7]. T cells play an integral role in the initiation and progression of the pathogenesis observed in Id3 −/− mice, as shown through T cell transfer experiments and T cell specific deletion of Id3 −/− [7, 8]. It still remains unclear how T cells influence gland function prior to significant tissue infiltration.…”
Section: Introductionmentioning
confidence: 98%
“…Csf1r MeriCreMer , Csf1r iCre , Rosa26 YFP-LSL , Cx 3 cr1 gfp/+ and Tnfrsf11a Cre mice (2, 5, 22, 35) and Id3 −/− ; Id1 fl/fl and Id3 f/f mice -kindly provided by R. Benezra (34, 36, 37)- were maintained under SPF conditions. Animal procedures were performed in adherence to our project licence issued by the United Kingdom Home Office under the Animals (Scientific Procedures) Act 1986 and by the Institutional Review Board (IACUC 15-04-006) from MSKCC.…”
Section: Methodsmentioning
confidence: 99%
“…The ablation of T cells brought about by neonatal thymectomy in Id3 KO resulted in normal secretory function [122]. The T cell lineage-specific Id3 conditional knockout mouse (Id3 f/f ; LekCre) exhibited similar phenotypic features to the C57BL/6- Id3 −/− mouse model with the exception of anti-SSA/Ro and anti-SSB/La autoantibodies, suggesting that an acquired mutation in developing T cells may induce a SjS-like condition [123]. However, a clinical study reported that primary SjS patients, mainly Caucasians, showed normal Id3 gene expression in salivary glandular epithelial cells, labial salivary glands and peripheral T cells[124].…”
Section: Mouse Modelsmentioning
confidence: 99%